Pengaruh Daun Pandan Wangi (Pandanus Ammarylifollius Roxb) sebagai Kosmetik Hair Tonic untuk Perawatan Rambut Berketombe - Zahra Zegita; Merita Yanita (Jurnal Kajian dan Penelitian Umum, 2024)
This research is motivated by scalp and hair disorders that affect beauty. Hair is generally considered a crown for every woman. One of the issues with the scalp and hair is dandruff. The factors causing dandruff include poor hair hygiene and the use of inappropriate hair cosmetics. Therefore, there needs to be an alternative to reduce dandruff, such as using hair tonic. The purpose of this study is to analyze a hair tonic made from pandan leaves with treatment frequencies of once a day and twice a day for two weeks.This type of research employs a quasi-experimental method. The design used is a Non-equivalent Control Group. The population for this study consists of women aged 19-24, specifically students from the Class of 2020 in Beauty and Makeup, with a sample size of 6. The data collection techniques include observation and documentation. The data analysis techniques used are normality tests, homogeneity tests, and t-tests. Based on the research results, the use of hair tonic made from pandan leaves (Pandanus amaryllifolius Roxb) as a cosmetic hair tonic for treating dandruff shows that in the indicator of the amount of flakes/dandruff, the treatment of once a day resulted in an average category of 5 (no flakes) while the treatment of twice a day resulted in an average category of 4 (significant reduction in dandruff). The average results indicate that the once-a-day hair tonic treatment is more effective in reducing dandruff.